فقہ ظاہری کا اصولِ اجتہاد (دلیلِ اجماعی ) مسالکِ اربعہ کے تناظر میں : The Principle of Ijtihaad in Fiqh Zahiri (Daleel e Ijmaa,i) In the perspective of Masaalik e Arba,a - Manhaj ud Din, Manhaj ud Din; Hashmi, Prof. Dr. Shah Mohyuddin (Al-Irfan, 2023)
ABSTRACT Islam is the religion which guides the humanity not only in every aspect of life, but also solves the problems coming to be faced by humans upto the Day of judgement. On the other side, as the texts of Quran and Hadith are limited, and the expected problems are unlimited, so it is impossible to denote the solution of every problem clearly and vividly in the texts of Holy Quran and Hadith. For this purpose , Quran and Hadith put some principles explicitly or inexplicitly through which the solution of every problem may be solved in the light of the Holy Quran and Hadith. This activity is called Ijtihaad and the principles are called Principles of Ijtihaad. The article below is related to a principle of Ijtihaad practiced in Fiqh Zahiri (Daleel e ijma,ai) and it answers to the question what is the position of Daleel e ijma,ai in the perspective of Masaalik e Arba,a.?